2000
DOI: 10.1080/09540120050001832
|View full text |Cite
|
Sign up to set email alerts
|

Risk behaviours for HIV and hepatitis infection among anabolic-androgenic steroid users

Abstract: This study examined HIV and hepatitis risk behaviours among anabolic-androgenic steroid (AAS) users and controls, providing a detailed assessment of both injection and sexual practices. Fifty AAS-using and 40 non-AAS-using weight trainers completed a semi-structured interview followed by a detailed questionnaire. The 'high risk' behaviour of sharing needles and syringes was not current practice among the AAS-using sample, with only one user reporting sharing injecting equipment in the past. However, for some u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 0 publications
5
26
0
Order By: Relevance
“…This contrasts with the substantially higher rates of RNSS among PWID surveyed in 2013: 14% and 16% reporting RNSS just in the previous month among NSW (Iversen et al, 2014a) and KRC (Iversen, Chow, & Maher, 2014b) participants in the ANSPS, their HCV prevalence being 54% and 73% respectively. This difference in injecting risk behaviour between the PIEDs injector subpopulation and PWID more generally is consistent with other study findings to date (Bolding et al, 1999(Bolding et al, , 2002Crampin et al, 1998;Day et al, 2008;Hope et al, 2013;Iversen et al, 2013;Larance et al, 2008;Midgley et al, 2000). However it contrasts sharply with the findings of the 2014 NNEDC survey wherein 11% of PIEDs injectors reported RNSS the past month, which was quite comparable to 13% RNSS reported for the PWID population surveyed overall, warranting further investigation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This contrasts with the substantially higher rates of RNSS among PWID surveyed in 2013: 14% and 16% reporting RNSS just in the previous month among NSW (Iversen et al, 2014a) and KRC (Iversen, Chow, & Maher, 2014b) participants in the ANSPS, their HCV prevalence being 54% and 73% respectively. This difference in injecting risk behaviour between the PIEDs injector subpopulation and PWID more generally is consistent with other study findings to date (Bolding et al, 1999(Bolding et al, , 2002Crampin et al, 1998;Day et al, 2008;Hope et al, 2013;Iversen et al, 2013;Larance et al, 2008;Midgley et al, 2000). However it contrasts sharply with the findings of the 2014 NNEDC survey wherein 11% of PIEDs injectors reported RNSS the past month, which was quite comparable to 13% RNSS reported for the PWID population surveyed overall, warranting further investigation.…”
Section: Discussionsupporting
confidence: 81%
“…McVeigh et al noted a six-fold increase in the number of new clients using anabolic steroids in British NSPs from 1991 to 2001 (McVeigh, Beynon, & Bellis, 2003). Previous studies in the UK had found varying prevalence of injecting risk behaviours, use and injection of psychoactive drugs, and sexual behaviours among PIEDs injectors (Bolding, Sherr, & Elford, 2002;Bolding, Sherr, Maguire, & Elford, 1999;Crampin et al, 1998;Midgley et al, 2000). But these were small samples, which did not specifically examine the prevalence of HIV and HCV in this group.…”
Section: Introductionmentioning
confidence: 86%
“…The prevalence of ever sharing injecting equipment in these studies ranged from 0.3% to 6%,20 28––30 32 but in one study it was 20% 33. The sharing of drug vials was more common (2.4%35; 9.9%34; 23%32). Studies elsewhere have found similar levels of equipment sharing 6 8.…”
Section: Introductionmentioning
confidence: 81%
“…These studies were mostly small (N<100), and typically recruited through gyms,28–33 with two recruiting gay men 34 35. The prevalence of ever sharing injecting equipment in these studies ranged from 0.3% to 6%,20 28––30 32 but in one study it was 20% 33. The sharing of drug vials was more common (2.4%35; 9.9%34; 23%32).…”
Section: Introductionmentioning
confidence: 99%
“…Injection occurs into large muscle groups (buttocks, thigh, or shoulder) or subcutaneously, but not intravenously. Needle sharing is reportedly uncommon, but does occur [13]. Users typically take steroids in "cycles" of 6 to 12 weeks, followed by 6 to 12 weeks off AAS, although longer cycles of use occur.…”
Section: Patterns Of Nonmedical Usementioning
confidence: 95%